(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2024)
This theoretical paper explores how the notion of teachers’ identities is defined and operationalised under multiple theoretical approaches, particularly in studies on language diversity. To explore this, the notion of teachers’ professional identity is first discussed as dealt with in mathematics education studies and other educational fields, addressing the related concepts considered essential to identity. Next, the paper outlines how these concepts become operational in specific examples of empirical studies in education and mathematics education. Based on this overview, new directions are proposed in researching teachers’ identities for addressing issues of language diversity in mathematics education.